2014
DOI: 10.1002/jcla.21746
|View full text |Cite
|
Sign up to set email alerts
|

Can Procalcitonin in Cerebrospinal Fluid be a Diagnostic Tool for Meningitis?

Abstract: PCT values in CSF can be very helpful in distinguishing BM from VM and other noninfectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Interestingly, our data matched current findings as significant elevations in CSF procalcitonin were not detected until as late as 4 days post fever in patients with bacterial meningitis when compared with aseptic and nonmeningitis groups. Although the brain is a potential source for procalcitonin production in experimental sepsis, the current study suggested that procalcitonin is actually reduced (500 pg/mL) within all three patient groups (61). Interestingly, procalcitonin has been recently found to reduce lipopolysaccharide-induced cytokine release in human peripheral blood mononuclear cells, suggesting that procalcitonin may not play a role in initiating essential inflammatory responses to bacterial CNS infection (62).…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, our data matched current findings as significant elevations in CSF procalcitonin were not detected until as late as 4 days post fever in patients with bacterial meningitis when compared with aseptic and nonmeningitis groups. Although the brain is a potential source for procalcitonin production in experimental sepsis, the current study suggested that procalcitonin is actually reduced (500 pg/mL) within all three patient groups (61). Interestingly, procalcitonin has been recently found to reduce lipopolysaccharide-induced cytokine release in human peripheral blood mononuclear cells, suggesting that procalcitonin may not play a role in initiating essential inflammatory responses to bacterial CNS infection (62).…”
Section: Discussionmentioning
confidence: 82%
“…Through a proposed cytokine-induced ubiquitous extrathyroidal upregulation of CALC-1 gene expression, bacterial infections induce a pervasive PCT release from hepatocytes, adipocytes and various other parenchymal cells [11]. Because of the cytokine-induced recruitment of PCT-producing cells, it has been suggested that its serum levels may reflect disease severity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [24,26,40] have assessed the diagnostic accuracy of PCT in CSF using the same cut-off value of 0.5 ng/mL. The reported sensitivities ranged from 0.55 to 1.0, and the reported specificities in the studies ranged from 0.93 to 1.0.…”
Section: Page 12 Of 25mentioning
confidence: 97%
See 1 more Smart Citation
“…An evaluation of PCT CSF:plasma ratios in patients with bacterial meningitis has not been done before. A recent study confirmed our results in CSF, but plasma levels were not included and therefore a direct comparison of PCT in CSF and plasma was lacking (Konstantinidis et al., 2015). The use of PCT in CSF in determining the need for and possibly duration of antibiotic treatment was beyond the scope of this study, but we hope our data will open the path to research in that direction.…”
Section: Discussionmentioning
confidence: 99%